Beneficial effects of Insulin and Rivastigmine in Type-3 Diabetes mellitus in rats - Abhilasha Ahlawat, Vaibhav Walia, Munish Garg (Journal of Applied Pharmaceutical Science, 2023)
Type-3 diabetes mellitus (T3D) is a pathological condition that possesses the characteristics of both Diabetes and Alzheimer’s disease, considered as brain diabetes. Treatment of T3D is still a challenging task for clinical practitioners. In this regard, this study was carried out to explore the effect of Insulin and Rivastigmine in the experimental rats. T3D was induced by administering streptozotocin (STZ; 35 mg/kg, i.p., single dose) followed by daily administration of aluminum chloride (AlCl3) (12.5 mg/kg, i.p. × 28 days). The Insulin (1 IU s.c. daily × 28 days) and Rivastigmine (1 mg/kg, i.p. × 28 days) treatment was given 30 minutes prior to administration of AlCl3. After 28 days of treatment, the rats were subjected to the estimation of various behavioral parameters using elevated plus maze (EPM) and Morris water maze (MWM) test and biochemical parameters including Insulin, glucose, malondialdehyde (MDA), nitrite, and amyloid beta (Aβ) levels. The results obtained revealed that the Insulin administration increased the square crossings in the open field, and reduced the transfer latency of T3D rats in the closed arm of EPM at day 2 and the frequency of platform crossing in the MWM test in T3D rats. The administration of Insulin and Rivastigmine reduced the blood glucose level and Aβ levels in the brain of T3D rats. Furthermore, Rivastigmine treatment also reduced the brain Insulin level of T3D rats. These studies indicate toward the beneficial effects of Insulin and Rivastigmine that open newer opportunities in the management protocol of T3D.